2014
DOI: 10.1016/j.tim.2014.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Glycan receptor specificity as a useful tool for characterization and surveillance of influenza A virus

Abstract: Influenza A viruses are rapidly evolving pathogens with the potential for novel strains to emerge and result in pandemic outbreaks in humans. Some avian-adapted subtypes have acquired the ability to bind to human glycan receptors and cause severe infections in humans but have yet to adapt to and transmit between humans. The emergence of new avian strains and their ability to infect humans has confounded their distinction from circulating human virus strains through linking receptor specificity to human adaptat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 92 publications
1
43
2
Order By: Relevance
“…Chicken cells are typically rich in α2,3-linked SA, whereas porcine cells are abundant in both α2,3- and α2,6-linked SAs (Raman et al , 2014). Our previous results have demonstrated that SV-A could recognize α2,3-linked SA as a receptor (Kim et al , 2016), suggesting that SV-A might be able to infect and induce pathology in both pigs and chicks.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chicken cells are typically rich in α2,3-linked SA, whereas porcine cells are abundant in both α2,3- and α2,6-linked SAs (Raman et al , 2014). Our previous results have demonstrated that SV-A could recognize α2,3-linked SA as a receptor (Kim et al , 2016), suggesting that SV-A might be able to infect and induce pathology in both pigs and chicks.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously demonstrated that SV-A could utilize α2,3-linked SA on GD1a glycolipid as a receptor (Kim et al , 2016). Indeed, glycolipid-associated α2,3-terminal SA is abundant on the cell surface of both avian and porcine species (de Graaf & Fouchier, 2014; Raman et al , 2014). However, our results in this study revealed that SV-A infection was limited to cells of porcine origin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…epistasis and other complexities that prevent straightforward prediction of viral traits from genotype (Russell et al, 2014; Kryazhimskiy et al, 2011; Gong and Bloom, 2014; Bloom et al, 2010; Wu et al, 2016; Raman et al, 2014; Tharakaraman et al, 2013; Gong et al, 2013);…”
Section: Introductionmentioning
confidence: 99%
“…Using X-ray co-crystal structures or modeled structural complexes of HA-glycan receptors, molecular features have been defined as distinct networks of inter-residue interactions involving key residues that make contacts with the different glycan receptor topologies. These features go beyond hallmark residue analyses and more accurately predict how amino acid variations in the receptor binding site impact the inter-residue interactions and glycan receptor binding specificity (Raman et al, 2014). Similarly, network analysis of amino acid residues predicted to have significant interactions has shown that antigenic sites on the HA interact with residues controlling glycan receptor binding specificity, and that changes in these antigenic residues can then lead to changes in receptor-binding affinity (Soundararajan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%